Modification of associations between ambient PM2.5 and vital signs by β-blocker prescription status among individuals with heart failure - Morgan Narain; Miyuki Breen; Alex P. Carll; Mehdi Hazari; Aimen Farraj; Cavin K. Ward-Caviness (Environmental Health)
Abstract Background Fine particulate matter (PM2.5) is associated with cardiovascular morbidity, especially among individuals with pre-existing cardiovascular conditions, such as heart failure (HF). Medical management with β-blockers may modify the association between PM2.5 and heart rate (HR) as β-blockers act on similar neurophysiologic pathways as PM2.5. Methods To examine potential medication-PM2.5 interactions, we utilized electronic health records (EHRs) from 26,653 individuals with HF in North Carolina observed from 2014 to 2016. Linear mixed effect models with a random intercept for individual were adjusted for individual and census level demographics and socioeconomic confounders. We examined 0-4-daily PM2.5 lags as well as the 5-day moving average. We stratified observations based β-blocker prescription status and quantified differences using a multiplicative interaction model. We also utilized data from an in vivo study of diesel exhaust exposure and β-blocker usage in HF prone rats to validate results and examine additional outcomes unavailable in the EHR data. Results Stratified analyses and the multiplicative interaction model revealed a significant difference in the association between PM2.5 and HR based on β-blocker prescription status. For 5-day average PM2.5 we observed a significant interaction (β interaction = -0.68, 95% CI: -0.82, -0.55) indicating that the association between PM2.5 and HR decreased for observations occurring after prescription of a β-blocker to study participants. This observation was reflected in the in vivo study as well. Conclusions β-blocker usage likely attenuates associations between short-term PM2.5 and HR. Accounting for this in future studies may reveal novel means of reducing PM2.5-related cardiovascular morbidity and reduce confounding in population with high rates of β-blocker usage.